(3eNJUQ GdGSJjYGH aj eYQaI GdCUMGHs - (3eMeO Hf YeGO GdOjf Hf TQa GdOjf Hf YHO GdeLjO LfLis; (3GHf YHO GdHQ , CHh YeQ jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj,J (B463 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe GdMGaX CHh YeQ Hf YHO GdHQ ai cJGH eYQaI GdUMGHI ef JUfjag s
(3hbO CVGa Edjg RjGOGJ dCHi fYje GdCUagGfi ai BNQ cd HGHs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs